PENGARUH PENGGUNAAN PUPUK ANORGANIK DAN ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - M.Syufrin Pasaribu; Hasmawi Hasyim; Hardi Winata (AGRIUM: Jurnal Ilmu Pertanian, 2012)
AbstactThis study aims to determine the response of growth and production of onion crop from inorganic fertilizer and organic fertilizer with Group Randomized Factorial Design with two factors studied. The results showed that the provision of inorganic fertilizers significantly affect plant height parameter (the highest plant shown in A1, ie 31.31 cm at age 6 weeks after planting), number of leaves (most leaves are shown in A3, which is 22.00 strands at age 7 weeks after planting), root wet weight of plant samples (tuber toughest shown in A1, which is 141.71 g), tuber dry weight of plant samples (tuber toughest shown in A1, ie 74.58 g) and showed different results are not evident in the number of samples of plant bulbs, plant bulbs perplot number, tuber weight and wet weight of plant perplot perplot plant dry bulbs. On the provision of organic fertilizer significantly affect plant height parameter (the highest plant shown in O1, ie 31.54 cm at age 6 weeks after planting), number of leaves (largest leaf shown in O0, ie 21.33 strands at the age of 7 weeks after planting ), the number of tubers plant samples (tuber ever shown in O3, which is 4.33 bulb), wet weight of plant sample bulbs (tubers toughest shown in O1, which is 142.07 g), tuber dry weight of plant samples (tuber toughest shown in O1 , ie 74.83 g) and showed different results are not evident in the number of tubers perplot plants, tuber weight and wet weight of plant perplot perplot plant dry bulbs. While the interaction between inorganic fertilizer and organic fertilizer showed different effects are not significant at all observation parameters.Keywords:inorgnanic and organic fertilizer, growth, production, Allium ascalonicum L.